Honest Signals of Status: Facial and Bodily Dominance Are Related to Success in Physical but Not Nonphysical Competition. (24th July 2019) - Kordsmeyer, Tobias L.; Freund, Daniel; Vugt, Mark van; Penke, Lars
Recent studies suggest that both facial and bodily dominance promote high status positions and predict status-seeking behaviors such as aggression and social dominance. An evolutionarily relevant context in which associations between these dominance signals and status outcomes may be prevalent are face-to-face status contests. The present study examined whether facial and bodily dominance predicted success in dyadic competitions (one physical discipline, arm wrestling, and three nonphysical disciplines) in men ( N = 125) in a controlled laboratory setting. Men's bodies and faces were independently rated for physical dominance, and associations of these ratings with contest outcomes as well as mediating and moderating variables (such as physical strength, body height, trait dominance, baseline and reactive testosterone) were examined. Both facial and bodily dominance positively predicted success in the physical discipline, mediated by physical strength, but not in the three nonphysical disciplines. Our findings demonstrate that facial and bodily physical dominance may be honest signals for men's formidability and hence status potential, at least in a physically competitive context.